(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
This paper provides an example of how it is possible to work intensively from an existential-phenomenological perspective with a client presenting in the context of a student counselling service. While the client did not initially appear to be a candidate for this type of therapy, it will be seen that the quality of relationship and a flexible approach to frame provided an opportunity for potentially transformative work with presenting issues relating to culture shock and sedimented self-construct within a single session.